A high‐content drug screening strategy to identify protein level modulators for genetic diseases: A proof‐of‐principle in autosomal dominant leukodystrophy. Issue 1 (8th December 2020) - Giorgio, Elisa; Pesce, Emanuela; Pozzi, Elisa; Sondo, Elvira; Ferrero, Marta; Morerio, Cristina; Borrelli, Giusy; Della Sala, Edoardo; Lorenzati, Martina; Cortelli, Pietro; Buffo, Annalisa; Pedemonte, Nicoletta; et al.
Abstract: In genetic diseases, the most prevalent mechanism of pathogenicity is an altered expression of dosage‐sensitive genes. Drugs that restore physiological levels of these genes should be effective in treating the associated conditions. We developed a screening strategy, based on a bicistronic dual‐reporter vector, for identifying compounds that modulate protein levels, and used it in a pharmacological screening approach. To provide a proof‐of‐principle, we chose autosomal dominant leukodystrophy (ADLD), an ultra‐rare adult‐onset neurodegenerative disorder caused by lamin B1 ( LMNB1 ) overexpression. We used a stable Chinese hamster ovary (CHO) cell line that simultaneously expresses an AcGFP reporter fused to LMNB1 and a Ds‐Red normalizer. Using high‐content imaging analysis, we screened a library of 717 biologically active compounds and approved drugs, and identified alvespimycin, an HSP90 inhibitor, as a positive hit. We confirmed that alvespimycin can reduce LMNB1 levels by 30%–80% in five different cell lines (fibroblasts, NIH3T3, CHO, COS‐7, and rat primary glial cells). In ADLD fibroblasts, alvespimycin reduced cytoplasmic LMNB1 by about 50%. We propose this approach for effectively identifying potential drugs for treating genetic diseases associated with deletions/duplications and paving the way toward Phase II clinical trials. Abstract : We developed a screening strategy, based on a bicistronic dual‐reporter vector, for identifying compounds that modulate protein levels, and used it in a pharmacological screening approach. This approach can be exploited to identify potential drugs for treating genetic diseases associated with deletions/duplications or other genetic and multifactorial disorders where the modulation of a protein represents a promising therapeutic option.